Morphosemantics in Infa'ala Patterned Verbs in The Al-Munawwir Dictionary by K.H. Ahmad Warson Munawwwir - Atikah Atikah; Arief Fiddienika; Mardhiana Jamal (Insyirah: Jurnal Ilmu Bahasa Arab dan Studi Islam, 2025)
VTAu2 pattern VII Infa'ala is one of the Arabic triliteral verbs with augmented affixes.  This research is language research that aims to find out the meanings formed from the process of affixation VTAu2 pattern VII Infa'ala in the Al-Munawwir Dictionary. Data collection uses the see-through method with tapping techniques and advanced techniques in the form of recording techniques. The data of this study is VTAu2 pattern VII Infa'ala in the Al-Munawwir Dictionary. This study uses the distribution method as a data analysis method. The data analysis technique uses the technique for direct elements (BUL) as the basic technique while the advanced technique uses the missing technique and the mark reading technique. Based on the results of the research from data collection and analysis of 620 VTAu2 pattern VII data, the researcher classified ten meanings with details: 1) the meaning of the consequences of VDT amounted to 390 data; 2) means aslul fi’il totals 190 data; 3) means reaching something amounting to 1 data; 4) means equal to its VDT totaling 3 data; 5) means superlatives totaling 3 data; 6) means reciprocal totaling 2 data; 7) VTAu2 pattern means compulsion totaling 3 data.; 8) means stating a repeating action totaling 3 data; 9) means the similarity amounting to 1 data; 10) means the same as af'ala totaling 3 data.